Converting FENO by different flows to standard flow FENO. (3rd June 2019) - Lassmann‐Klee, Paul G.; Lehtimäki, Lauri; Lindholm, Tuula; Malmberg, Leo Pekka; Sovijärvi, Anssi R.A.; Piirilä, Päivi Liisa
Abstract: In clinical practice, assessment of expiratory nitric oxide ( F ENO ) may reveal eosinophilic airway inflammation in asthmatic and other pulmonary diseases. Currently, measuring of F ENO is standardized to exhaled flow level of 50 ml s −1, since the expiratory flow rate affects the F ENO results. To enable the comparison of F ENO measured with different expiratory flows, we firstly aimed to establish a conversion model to estimate F ENO at the standard flow level, and secondly, validate it in five external populations. F ENO measurements were obtained from 30 volunteers (mixed adult population) at the following multiple expiratory flow rates: 50, 30, 100 and 300 ml s −1, after different mouthwash settings, and a conversion model was developed. We tested the conversion model in five populations: healthy adults, healthy children, and patients with COPD, asthma and alveolitis. F ENO conversions in the mixed adult population, in healthy adults and in children, showed the lowest deviation between estimated F ^ ENO from 100 ml s −1 and measured F ENO at 50 mL s −1 : −0·28 ppb, −0·44 ppb and 0·27 ppb, respectively. In patients with COPD, asthma and alveolitis, the deviation was −1·16 ppb, −1·68 ppb and 1·47 ppb, respectively. We proposed a valid model to convert F ENO in healthy or mixed populations, as well as in subjects with obstructive pulmonary diseases and found it suitable for converting F ENO measured with different expiratory flows to the standard flow in large epidemiological data, but not on individual level. In conclusion, a model to convert F ENO from different flows to the standard flow was established and validated.